STRATEGI PENGEMBANGAN UMKM DI KELURAHAN MANUKAN KULON MELALUI WORKSHOP PEMANFATAAN DIGITALISASI - Puspa Arum, Dewi; Munazilah, Siti Nur; Rahmadiani, Mulia; Twin Ramadhisa, Roro Desy; Karimah, Rizqi; Amelia Santoso, Rosanya; Maria Febryanti, Christin; Nur Abifah, Serlia; Visan Rahmaddani, Fakhri; Dirga Safalas, Malta; Paulina Situmorang, Sinta (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
The rapid development that is increasingly sophisticated in modern times like this is very important for MSME (Micro Small and Medium Enterprises) actors to start utilizing digital technology as a means to develop their MSME business.In Manukan Kulon Village, Kec. Tandes, Surabaya City is an area that has various types of MSME that are developing.What is meant by developing is that MSME actors in Manukan Kulon Village still do not understand and do not master the use of technology that has developed. This made the group of 43 KKN Tematik MBKM UPN “Veteran” East Java consisting of 10 members held a Training Workshop on the digitization of MSMEs for MSME actors in Manukan Kulon Village. The training materials include digital marketing, digital payments, and product photos.The method of implementing a training workshop with the theme Improving Business Quality Through Digitizing MSME which took place at the Manukan Kulon Village Office.The training workshop provided by group of 43 KKN Tematik MBKM UPN “Veteran” East Java regarding the digitization of MSME has succeeded in changing MSME in Manukan Kulon which were initially still conventional to digital. From the 15 MSMEs invited, there are two MSMEs that need more guidance, namely MSMEs Mak Mol Kitchen and Sari Lerak Sedjati. After being monitored, the two MSMEs succeeded in rebranding and posting creative product photos on their social media accounts, as well as with attractive Instagram feed designs for their potential customers. The group of 43 KKN Tematik MBKM hopes that this development can be maintained as well as a new beginning for MSME actors in Manukan Kulon Village to revive economic factors through digitalization.